Can the Ottawa knee rule be applied to children? A systematic review and meta-analysis of observational studies. Issue 4 (23rd March 2009) - Vijayasankar, D; Boyle, A A; Atkinson, P
Abstract : Background: The Ottawa knee rule (OKR), a clinical decision aid is used to reduce unnecessary radiography. It is not clear whether this rule can be applied to children. Objective: To establish whether the OKR had adequate sensitivity and acceptable specificity in children to advocate widespread use. Methods: A systematic review and meta-analysis was conducted of observational studies that examined the diagnostic characteristics of the OKR in children. Data sources: Relevant English language articles were identified from Medline (1950 to date), EMBASE (1974 to date), CINAHL (1982 to date), the Cochrane Library, Google Scholar and a hand search of bibliographies. Study selection: Observational studies that included children and have used the OKR for ruling out fractures in children either radiologically or in combination with follow-up. Results: Four relevant studies were identified. Three studies were suitable for inclusion in the meta-analysis, representing 1130 children. The pooled negative likelihood ratio was 0.07 (95% CI 0.02 to 0.29), the pooled positive likelihood ratio was 1.94 (95% CI 1.60 to 2.36), the pooled sensitivity was 99% (CI 94.4 to 99.8) and the pooled specificity was 46% (CI 43.0 to 49.1). The reduction in radiography was between 30% and 40%. Conclusion: The OKR has high sensitivity and adequate specificity for children over the age of 5 years. There are not enough good data to advocate application of the OKR in children less than 5 years.